2014
DOI: 10.3892/etm.2014.1969
|View full text |Cite
|
Sign up to set email alerts
|

In vivo ossification of a scaffold combining β-tricalcium phosphate and platelet-rich plasma

Abstract: Tricalcium phosphate (TCP) and platelet-rich plasma (PRP) are commonly used in bone tissue engineering. The aim of the present study was to investigate a composite that combined TCP with PRP and assess its effectiveness in the treatment of bone defects. Cavity-shaped bone defects were established on the tibiae of 27 beagle dogs, and were repaired by pure β-TCP with bone marrow stromal cells (BMSCs), β-TCP/PRP with BMSCs and autogenic ilium. The samples were harvested at 4, 8 and 12 weeks, and bone regeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
1
3
0
2
Order By: Relevance
“…However, PRP is difficult to store due to its liquid form. To address this difficulty, some studies have used bovine thrombin and calcium chloride to turn liquid PRP into a solid form [ 29 ]. Recently, PRP was developed into a gel form that was termed platelet-rich fibrin (PRF).…”
Section: Introductionmentioning
confidence: 99%
“…However, PRP is difficult to store due to its liquid form. To address this difficulty, some studies have used bovine thrombin and calcium chloride to turn liquid PRP into a solid form [ 29 ]. Recently, PRP was developed into a gel form that was termed platelet-rich fibrin (PRF).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the use of autologous PRP in bone regeneration represents a safe, simple, and cost-efficient approach that has positive effects on cell proliferation and migration [ 14 16 ], osteogenesis [ 17 19 ], and angiogenesis [ 20 , 21 ]. Consequently, the combined use of PRP and β-TCP has gained popularity in the field of bone tissue engineering for the combination of all properties required in an ideal bone graft material, including osteoinductivity, osteoconductivity, osteogenesis, and angiogenesis [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be used for small-sized defects without additional graft [ 53 ]. For the repair of large-sized defects, combination with calcium-based materials [ 54 ] or matrix protein [ 51 , 53 ] has been tested and used.…”
Section: Main Textmentioning
confidence: 99%